EVALUASI PROSES PEMBELAJARAN BERBASIS KURIKULUM MERDEKA BELAJAR ( STUDI ANALISIS DI SMK NEGERI 14 JAKARTA ) - Prayogi, Radi Ahnaf; Nahuda, Nahuda (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
Autonomy to create student-centered and contextual learning, including Islamic Religious Education (PAI) learning, is given by the Independent Curriculum to educational units. However, the implementation of this curriculum is full of obstacles, especially related to the process of evaluating student learning. The implementation of PAI learning based on the Independent Curriculum at SMKN 14 Jakarta will be evaluated, along with the challenges faced by teachers and the evaluation techniques used. This study uses an evaluative technique that combines formative and summative assessments along with descriptive qualitative methodology. Information was collected through recording the implementation of learning assessments, in-depth interviews with vice principals and educators, and observations. According to the research findings, the learning assessment process has been based on the principles of Independent Curriculum, which includes flexible scheduling and technology evaluation techniques such as Google Forms. The main challenges include differences in students' understanding of the subject matter, lack of helpful criticism, and lack of learning time. Although teacher feedback techniques still vary from one-way to more reflective and interactive, peer counseling strategies are used to address student ability inequalities. The successful implementation of this curriculum depends on a number of elements, including parent and school support, availability of technology, and instructor competence. The conclusions of this study emphasize that comprehensive learning assessment must take into account the various characteristics of students and emphasize the importance of two-way communication in the teaching and learning process. Building a learning environment that encourages student character growth requires the use of a respectful and humanistic approach.